5.11.6 Problems 501 to 600

Table 5.813: Third and higher order homogeneous ODE

#

ODE

Mathematica

Maple

14043

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+10 y^{\prime } = 0 \]

14044

\[ {}y^{\prime \prime \prime \prime }+13 y^{\prime \prime }+36 y = 0 \]

14158

\[ {}y^{\prime \prime \prime }+\frac {3 y^{\prime \prime }}{x} = 0 \]

14225

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

14235

\[ {}y^{\prime \prime \prime } = {y^{\prime \prime }}^{2} \]

14236

\[ {}y^{\prime } y^{\prime \prime \prime }-3 {y^{\prime \prime }}^{2} = 0 \]

14246

\[ {}y^{\prime \prime \prime \prime }-5 y^{\prime \prime }+4 y = 0 \]

14247

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

14248

\[ {}y^{\prime \prime \prime }-3 a y^{\prime \prime }+3 a^{2} y^{\prime }-y a^{3} = 0 \]

14249

\[ {}y^{\left (5\right )}-4 y^{\prime \prime \prime } = 0 \]

14250

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+9 y = 0 \]

14251

\[ {}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+16 y = 0 \]

14252

\[ {}y^{\prime \prime \prime \prime }+y = 0 \]

14253

\[ {}y^{\prime \prime \prime \prime }-a^{4} y = 0 \]

14325

\[ {}y^{\prime \prime \prime }-7 y^{\prime \prime }+12 y^{\prime } = 0 \]

14344

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = 0 \]

14491

\[ {}y^{\prime \prime \prime }+y^{\prime } = 0 \]

14497

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }+6 y^{\prime }-4 y = 0 \]

14498

\[ {}y^{\prime \prime \prime \prime }-16 y = 0 \]

14499

\[ {}y^{\prime \prime \prime \prime }+16 y = 0 \]

14500

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+8 y^{\prime \prime }-8 y^{\prime }+4 y = 0 \]

14501

\[ {}y^{\prime \prime \prime \prime }-8 y^{\prime } = 0 \]

14502

\[ {}36 y^{\prime \prime \prime \prime }-12 y^{\prime \prime \prime }-11 y^{\prime \prime }+2 y^{\prime }+y = 0 \]

14503

\[ {}y^{\left (5\right )}-3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime } = 0 \]

14504

\[ {}y^{\left (5\right )}-y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+35 y^{\prime \prime }+16 y^{\prime }-52 y = 0 \]

14505

\[ {}y^{\left (8\right )}+8 y^{\prime \prime \prime \prime }+16 y = 0 \]

14507

\[ {}y^{\prime \prime \prime }+\left (-3-4 i\right ) y^{\prime \prime }+\left (-4+12 i\right ) y^{\prime }+12 y = 0 \]

14508

\[ {}y^{\prime \prime \prime \prime }+\left (-3-i\right ) y^{\prime \prime \prime }+\left (4+3 i\right ) y^{\prime \prime } = 0 \]

14517

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }-4 y^{\prime }+12 y = 0 \]

14518

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime \prime }+2 y^{\prime }-y = 0 \]

14542

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+4 y^{\prime }-4 y = 0 \]

15224

\[ {}y^{\prime \prime \prime } = y^{\prime \prime } \]

15226

\[ {}y^{\prime \prime \prime } = 2 \sqrt {y^{\prime \prime }} \]

15227

\[ {}y^{\prime \prime \prime \prime } = -2 y^{\prime \prime \prime } \]

15247

\[ {}y^{\prime \prime \prime } = y^{\prime \prime } \]

15267

\[ {}y^{\prime \prime \prime }+y = 0 \]

15271

\[ {}y y^{\prime \prime \prime }+6 y^{\prime \prime }+3 y^{\prime } = y \]

15292

\[ {}y^{\prime \prime \prime }-9 y^{\prime \prime }+27 y^{\prime }-27 y = 0 \]

15294

\[ {}y^{\prime \prime \prime \prime }-8 y^{\prime \prime \prime }+24 y^{\prime \prime }-32 y^{\prime }+16 y = 0 \]

15295

\[ {}x^{3} y^{\prime \prime \prime }-4 y^{\prime \prime }+10 y^{\prime }-12 y = 0 \]

15307

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = 0 \]

15308

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

15313

\[ {}y^{\prime \prime \prime }-9 y^{\prime } = 0 \]

15314

\[ {}y^{\prime \prime \prime \prime }-10 y^{\prime \prime }+9 y = 0 \]

15353

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime } = 0 \]

15354

\[ {}y^{\prime \prime \prime \prime }+4 y^{\prime \prime } = 0 \]

15355

\[ {}y^{\prime \prime \prime \prime }-34 y^{\prime \prime }+225 y = 0 \]

15356

\[ {}y^{\prime \prime \prime \prime }-81 y = 0 \]

15357

\[ {}y^{\prime \prime \prime \prime }-18 y^{\prime \prime }+81 y = 0 \]

15358

\[ {}y^{\left (5\right )}+18 y^{\prime \prime \prime }+81 y^{\prime } = 0 \]

15359

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }+y^{\prime }-y = 0 \]

15360

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = 0 \]

15361

\[ {}y^{\prime \prime \prime }-8 y^{\prime \prime }+37 y^{\prime }-50 y = 0 \]

15362

\[ {}y^{\prime \prime \prime }-9 y^{\prime \prime }+31 y^{\prime }-39 y = 0 \]

15363

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+2 y^{\prime \prime }+4 y^{\prime }-8 y = 0 \]

15364

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime }+10 y^{\prime \prime }+18 y^{\prime }+9 y = 0 \]

15365

\[ {}y^{\prime \prime \prime }+4 y^{\prime } = 0 \]

15366

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+12 y^{\prime }-8 y = 0 \]

15367

\[ {}y^{\prime \prime \prime \prime }+26 y^{\prime \prime }+25 y = 0 \]

15368

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime }+9 y^{\prime \prime }+9 y^{\prime } = 0 \]

15369

\[ {}y^{\prime \prime \prime }-8 y = 0 \]

15370

\[ {}y^{\prime \prime \prime }+216 y = 0 \]

15371

\[ {}y^{\prime \prime \prime \prime }-3 y^{\prime \prime }-4 y = 0 \]

15372

\[ {}y^{\prime \prime \prime \prime }+13 y^{\prime \prime }+36 y = 0 \]

15373

\[ {}y^{\left (6\right )}-3 y^{\prime \prime \prime \prime }+3 y^{\prime \prime }-y = 0 \]

15374

\[ {}y^{\left (6\right )}-2 y^{\prime \prime \prime }+y = 0 \]

15375

\[ {}16 y^{\prime \prime \prime \prime }-y = 0 \]

15376

\[ {}4 y^{\prime \prime \prime \prime }+15 y^{\prime \prime }-4 y = 0 \]

15377

\[ {}y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+16 y^{\prime }-16 y = 0 \]

15378

\[ {}y^{\left (6\right )}+16 y^{\prime \prime \prime }+64 y = 0 \]

15403

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-4 x y^{\prime }+4 y = 0 \]

15404

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

15405

\[ {}x^{3} y^{\prime \prime \prime }-5 x^{2} y^{\prime \prime }+14 x y^{\prime }-18 y = 0 \]

15406

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+7 x y^{\prime }-8 y = 0 \]

15407

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+15 x^{2} y^{\prime \prime }+9 x y^{\prime }+16 y = 0 \]

15408

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }-9 x y^{\prime }+9 y = 0 \]

15409

\[ {}x^{4} y^{\prime \prime \prime \prime }+2 x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

15410

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+7 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

15542

\[ {}y^{\prime \prime \prime \prime }-8 y^{\prime \prime }+16 y = 0 \]

15547

\[ {}y^{\left (5\right )}-6 y^{\prime \prime \prime \prime }+13 y^{\prime \prime \prime } = 0 \]

15560

\[ {}y^{\prime \prime \prime \prime }-16 y = 0 \]

15798

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime } = 0 \]

15799

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0 \]

15824

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime } = 0 \]

15825

\[ {}y^{\prime \prime \prime }-4 y^{\prime } = 0 \]

15839

\[ {}y^{\prime \prime \prime \prime }+\frac {25 y^{\prime \prime }}{2}-5 y^{\prime }+\frac {629 y}{16} = 0 \]

16367

\[ {}y^{\prime \prime \prime } = 0 \]

16368

\[ {}y^{\prime \prime \prime }-10 y^{\prime \prime }+25 y^{\prime } = 0 \]

16369

\[ {}8 y^{\prime \prime \prime }+y^{\prime \prime } = 0 \]

16370

\[ {}y^{\prime \prime \prime \prime }+16 y^{\prime \prime } = 0 \]

16371

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

16372

\[ {}3 y^{\prime \prime \prime }-4 y^{\prime \prime }-5 y^{\prime }+2 y = 0 \]

16373

\[ {}6 y^{\prime \prime \prime }-5 y^{\prime \prime }-2 y^{\prime }+y = 0 \]

16374

\[ {}y^{\prime \prime \prime }-5 y^{\prime }+2 y = 0 \]

16375

\[ {}5 y^{\prime \prime \prime }-15 y^{\prime }+11 y = 0 \]

16376

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime \prime } = 0 \]

16377

\[ {}y^{\prime \prime \prime \prime }-9 y^{\prime \prime } = 0 \]

16378

\[ {}y^{\prime \prime \prime \prime }-16 y = 0 \]

16379

\[ {}y^{\prime \prime \prime \prime }-6 y^{\prime \prime \prime }-y^{\prime \prime }+54 y^{\prime }-72 y = 0 \]

16380

\[ {}y^{\prime \prime \prime \prime }+7 y^{\prime \prime \prime }+6 y^{\prime \prime }-32 y^{\prime }-32 y = 0 \]